ANALISIS KESELAMATAN DAN KESEHATAN KERJA TERHADAP KEPUASA KERJA PT. KALTIM PRIMA COAL SAMARINDA - Adi Suroso, Mukhrin, LCA.Robin Jonatan (EKONOMIA, 2016)
Analysis of Occupational Safety and Health Program on Job Satisfaction PT. Kaltim Prima Coal. This study aims to determine the Occupational Safety and Health Program on Job Satisfaction PT. Kaltim Prima Coal, and to know the company's policies in improving Occupational Health and Safety Program Employees.The population is all employees working on the production of coal transportation amounted to 442 people. The research sample, taken as many as 82 employees were determined by random sampling technique (random sample). The research data were obtained and analyzed descriptively.This study concluded that the Occupational Safety and Health Program (K3) are implemented on the company includes Guidance Safety and Employee Health Development. Based on the analysis of data and discussion that has been done, it can be concluded that the program Occupational Health and Safety (K3) significant effect on employee job satisfaction. The keijakan that apply to the management company in an effort to improve the Occupational Health and Safety (K3) PT. Kaltim Prima Coal is to implement the program Occupational Health and Safety (K3), which includes the maintenance of the work environment, the provision of facilities / equipment occupational safety and health, as well as the fostering of human resources or the personnel employed at the company.